Poor glycemic control in younger women attending Malaysian public primary care clinics: findings from adults diabetes control and management registry - Ai, Theng Cheong; Ping, Yein Lee; Shariff-Ghazali, Sazlina; Bujang, Mohamad Adam; Boon, How Chew; Ismail, Mastura; Haniff, Jamaiyah; Syed Alwi, Syed-Abdul-Rahman; Taher, Sri Wahyu; Mat-Nasir, Nafiza (Biomed Central, 2013)
Abstract Background: Women of reproductive age are a group of particular concern as diabetes may affect their pregnancy outcome as well as long-term morbidity and mortality. This study aimed to compare the clinical profiles and glycemic control of reproductive and non-reproductive age women with type 2 diabetes (T2D) in primary care settings, and to determine the associated factors of poor glycemic control in the reproductive age group women. Methods: This was a cross-sectional study using cases reported by public primary care clinics to the Adult Diabetes